ANALYSIS OF ARTISTICALY CREATIVE WORK OF STUDENTS IN LATVIAN HIGHER EDUCATION DANCE PROGRAMS - Gorobeca, Paula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Often dance teachers do not realize that their professional activity is the creation of an artwork. Teachers are limited to a range of movements in some genres or the requirements of their work place, but above all dance teachers are representatives of art un they have a potential to create new, original artistic value and contribute to the art and cultural space in Latvia. Therefore it is essential to understand the development and level of artistically creative work in the study process. The aim of this article is to analyse the artistically creative work of students in different higher education dance programs. The aim is carried out in the analysis of literature and on its base promoted evaluation indicators and levels of artistically creative work for dance teachers as choreographers. A questionnaire is designed on a basis of these indicators and levels. The respondents are students in higher education dance programs in Latvian Academy of Music and Latvian Academy of Culture. The results promote strong and weak points in the artistically creative work of students as well as the necessary discussable questions in the study process.